'In vitro' assessments of microencapsulated viable cells as a result of primary bile acid-encapsulated formulation for inflammatory disorders - Mooranian Armin; Jones Melissa; Walker Daniel; Ionescu Corina Mihaela; Wagle Susbin Raj; Kovačević Božica; Chester Jacqueline; Foster Thomas; Johnston Edan; Mikov Momir; Al-Salami Hani (Scripta Medica, 2022)
Background / Aim: Metformin is widely used in type 2 diabetes and exhibits many positive biological effects on pancreatic b-cells and muscle cells, such as supporting insulin release by b-cells and glucose uptake by muscle cells and reducing oxidative stress, particularly due to diabetes-associated hyperglycaemia. Interestingly, for type 1 diabetes, transplantation of healthy b-cells has been proposed as a novel way to replace insulin therapy. Recently, bile acid-formulations containing transplantable b-cells showed best stability. Hence, this study aimed to explore the effects of metformin-bile acid formulations in b-cell encapsulation and on the biological activities of b-cells and muscle-cells. Methods: Two sets of biological effects were examined, using metformin-bile acid formulations, on encapsulated b-cells and on muscle cells exposed to the formulations. Results: Various encapsulated b-cell formulations' cell viability, insulin levels, cellular oxidative stress, cellular inflammatory profile and bioenergetics at the normoand hyperglycaemic states showed differing results based upon the metformin concentration and the inclusion or absence of bile acid. Similar effects were observed with muscle cells. Low ratios of metformin and bile acids showed best biological effects, suggesting a formulation dependent result. The formulations' positive effects were more profound at the hyperglycaemic state suggesting efficient cell protective effects. Conclusion: Overall, metformin had positive impacts on the cells in a concentration-dependent manner, with the addition of chenodeoxycholic acid further improving results.